2011
DOI: 10.1182/blood-2011-04-346767
|View full text |Cite
|
Sign up to set email alerts
|

MSI2 protein expression predicts unfavorable outcome in acute myeloid leukemia

Abstract: MSI2 is highly expressed in human my

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 34 publications
6
88
2
Order By: Relevance
“…These data further suggest that measuring bulk expression in primary leukemias may not provide insight into the requirement for MSI2 within a particular patient. This point is strengthened by immunohistochemical examination of protein expression of MSI2 in AML patient bone marrow biopsies, in which demonstration of elevated MSI2 in as little as >1% of the cell population could still predict an unfavorable outcome (17). Therefore, it will be important to determine whether proteinbased approaches to measure MSI2 combined with known stem cell markers can be used to predict survival or alter the therapeutic strategy in the various subtypes and genetic alterations that characterize AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data further suggest that measuring bulk expression in primary leukemias may not provide insight into the requirement for MSI2 within a particular patient. This point is strengthened by immunohistochemical examination of protein expression of MSI2 in AML patient bone marrow biopsies, in which demonstration of elevated MSI2 in as little as >1% of the cell population could still predict an unfavorable outcome (17). Therefore, it will be important to determine whether proteinbased approaches to measure MSI2 combined with known stem cell markers can be used to predict survival or alter the therapeutic strategy in the various subtypes and genetic alterations that characterize AML.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that increased expression of MSI2 may predict aggressiveness in a variety of cancers. In summary, MSI2 expression was found to be an independent adverse prognostic marker in AML and is a critical regulator of HSC maintenance, which contributes to the pathogenesis of leukemia when dysregulated (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…40 A recent study demonstrated that MSI2 protein expression predicts unfavorable outcome in AML. 41 It was surprising that survivin levels negatively correlated with MAPK signaling, and multiple proteins related to cell migration/adhesion, since we and others have shown that survivin expression is induced by MAPK/ERK signaling 5 and that survivin was reported to activate NF-B in cooperation with XIAP (leading to fibronectin gene expression) and to regulate metastasis in epithelial tumors. 42 We believe that the correlation results are valid as survivin was negatively correlated with not just one but multiple proteins in the MAPK signaling pathway and various proteins related to cell migration/adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Msi2 expression was negatively Msi2 promotes bladder cancer metastasis via JAK2/STAT3 pathway C Yang et al associated with AML patients outcome, 21 while the expression of NUMB, which was negatively regulated by Msi2 both in vitro and in vivo, 19 was not associated with overall survival in AML patients. 22 Mu et al 23 reported that high Msi2 expression could indicate poor prognosis in adult B-cell acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%